2015
DOI: 10.2176/nmc.oa.2014-0280
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Transnasal Interseptal Approach for Invasive Clival Tumors: Development of an Approach Method Regarding Maximal Preservation of the Nasal Anatomy

Abstract: Asian people frequently show small noses, narrow nasal apertures, and congestive mucosa on the turbinates and septum. To reduce the risk of nasal morbidity with increased radicality for skull base tumors in these patients, we developed endoscopic transnasal interseptal approach (ETISA) in transsphenoidal surgery for invasive clival tumors (ICTs). Indication for ETISA is radical resection for tumors occupying deep ventral skull base regions, confined posterior to the level of the middle turbinates. After removi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
(34 reference statements)
1
21
0
1
Order By: Relevance
“…18,37 Also, it is easier to approach tumors that extensively involve the paramedian regions, such as the clivus, sphenoid sinus, and the nasopharyngeal region, or bilateral petrous apex, from the inside. 10,28,30,35,39 In our cases, most of the tumors extended to the inferolateral part of the petrous apex or the paramedian regions and were considered suitable for the ETAP approach. However, experience with intradural lesions remains limited, and for intracranial tumors without skull base invasion, the transcranial approach remains warranted for safe surgical procedures at present.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…18,37 Also, it is easier to approach tumors that extensively involve the paramedian regions, such as the clivus, sphenoid sinus, and the nasopharyngeal region, or bilateral petrous apex, from the inside. 10,28,30,35,39 In our cases, most of the tumors extended to the inferolateral part of the petrous apex or the paramedian regions and were considered suitable for the ETAP approach. However, experience with intradural lesions remains limited, and for intracranial tumors without skull base invasion, the transcranial approach remains warranted for safe surgical procedures at present.…”
Section: Discussionmentioning
confidence: 77%
“…While dissection and resection of the tumor mostly proceeded under the vision of angled endoscopes (30° or 70°), the nasal speculum specially designed for endoscopic transsphenoidal surgery allowed stable maintenance of a wide surgical corridor with maximum preservation of the nasal anatomy, facilitating swift delivery of surgical tools and a clear, bloodless surgical field. 30 To retain a sufficient surgical pathway, the retrocarotid window was enlarged along the petrooccipital fissure, minimizing the risk associated with skeletonization and mobilization of the ICA during the surgical procedure. Our results indicated that the transsphenoidal route was sufficient in a certain number of cases to approach the petrosal areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incision to the nasal septum mucosa First, we dissected the mucosa from the right nasal septum close to the vomer. 3,4 The exact same procedure was performed on the left side. The nasal speculum was applied in each nostril, and the vomer as well as bilateral sphenoid ostium were exposed.…”
Section: :06mentioning
confidence: 99%